ACUTE KIDNEY INJURY IN TETANUS PATIENTS AT INTENSIVE CARE UNIT OF A PEDIATRIC TERTIARY CARE HOSPITAL - Ayub, Faryal; Anjum, Misbah; Bibi, Safia; Khan, Aisha; Soomro, Shazia (Infectious Diseases Journal of Pakistan, 2022)
Background: Tetanus is one of the fatal diseases and is amongst major health problems in developing countries. Acute kidney injury (AKI) is a common and lethal complication of tetanus and has a direct association with tetanus mortality. To determine the frequency of acute kidney injury (AKI) in tetanus patients, hospitalized at pediatric intensive care unit (PICU) of a tertiary care hospital. Material and Methods: This prospective cross-sectional study was conducted from January 2020 to December 2020. Diagnosed tetanus patients hospitalized at PICU of National Institute of child health were included in the study. Detailed history, clinical signs and symptoms were recorded and laboratory tests including serum urea and creatinine were performed on admission, at 48 hours and at 1 week. Input and output charting was documented. AKI was diagnosed and further categorized into Risk, Injury and Failure as per pRIFLE criteria. Data was analyzed using SPSS 25. Results: Total 52 patients with tetanus were enrolled. Mean age of patients was 8.56 + 2.57 years including 71.2% males and 28.8% females. Most common presentation was lock jaw in 90.4% and foot injury was the predominant (57.7%) site of trauma. AKI was seen in 13.46% at the time of admission and in 58.69% at 1st week, out of which 28.8% needed dialysis. Mortality was 34.6% and 5.8% developed chronic kidney disease. Higher rates of deaths were observed in patients who presented with a pRIFLE criteria of risk or injury at the time of admission (p-value 0.010). Conclusion: AKI is a common complication in tetanus patients and is associated with high mortality. Monitoring patients for AKI and implementation of pRIFLE criteria is important to find out patients at risk for AKI. Keywords: Tetanus, Acute kidney injury, Vaccination, pRIFLE